Progress in legislating domestic violence and gender based violence in Timor-Leste - Ferguson, Phyllis (Faculty of Social Sciences and Humanities, UKM,Bangi, 2011)
The present situation in Timor Leste can only be understood in the historical and cultural context of prior political subjugations. Gender violence is a domestic and community reality in Timor-Leste. It existed in Portuguese colonial times, during the invading Japanese occupation in 1942, during the revolution of 1974, in the 24-year of occupation by Indonesia, which left 180,000 dead and 40% of women and girls as survivors of rape or sexual assault, and since 1999 post-conflict until Independence. Further violence since independence occurred in Dili, the capital, in 2002, 2005, and intensively in 2006, 2007 and 2008. Today, new engines for DV (Domestic Violence) and SGBV (Sexual and Gender-Based Violence ) have replaced the previous subjugations of colonialism and military occupations. This paper gives an in-depth analysis of the DV and SGBV outstanding issues, challenges, development and prospects. For the world’s newest nation, much progress has been made in legislation promulgated since the restoration of independence in 2002. Now the need is for these various platforms of action to be pervasively socialised with all the citizens of Timor-Leste and for sustainable funding to be made available to achieve these goal. Despite these problems Timorese women have been granted legal empowerment and so been given hope for a better life.